1976
DOI: 10.1002/tera.1420140310
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of pinocytosis in rat yolk sac by trypan blue

Abstract: Day 17.5 yolk sacs from rats injected with partially denatured 125I-labeled bovine serum albumin (I-BSA) were cultured in vitro by a raft technique. The rates of release of [125I]iodotyrosine were similar in control yolk sacs and in yolk sacs from rats preinjected with trypan blue. Day 17.5 rat yolk sacs were also cultured in medium containing I-BSA. Following pinocytic uptake the substrate was degraded intracellularly and [135I]iodotyrosine released into the medium. Trypan blue, when present in the medium in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…The results (Fig. 4) show that for both (Williams, Roberts, Kidston, Beck & Lloyd, 1976;Field et al, 1977). Preliminary tests showed that the dye did not affect the development of embryos in vitro.…”
Section: Effect Ofprotein Concentrationmentioning
confidence: 75%
See 1 more Smart Citation
“…The results (Fig. 4) show that for both (Williams, Roberts, Kidston, Beck & Lloyd, 1976;Field et al, 1977). Preliminary tests showed that the dye did not affect the development of embryos in vitro.…”
Section: Effect Ofprotein Concentrationmentioning
confidence: 75%
“…This conclusion is supported by the electron microscopic studies of rat (Schlafke & Enders, 1973) and rabbit (Hastings & Enders, 1974) preimplantation embryos which show exogenous proteins in pinocytotic vesicles and bound to the membrane. Uptake was reversibly inhibited by trypan blue which has been described as a specific reversible inhibitor of pinocytosis (Williams et al, 1976;Field et al, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Since TB possibly does not go beyond the VE, we further examined whether fluorescence-labeled DNA/lipid complexes exhibit a distribution similar to that of TB. Fluorescence-labeled HaeIII-digested pBluescript SK(Ϫ) plasmid vector fragments were column-purified (Figure 6a) and mixed with FuGENE6.…”
Section: Gene Therapymentioning
confidence: 99%
“…distribution governed mainly by molecular weight-dependent extravasation and glomerular filtration (Seymour et al, 1987). Their slow accumulation by cells is via fluid-phase pinocytosis (Duncan et al, 1981), an uptake mechanism which is not saturable and where the amount of material captured is directly proportional to its concentration in the extracellular fluid (Williams et al, 1975a). In contrast, copolymers containing targeting residues (e.g.…”
Section: Assessment Of Release Of Liver Enzymesmentioning
confidence: 99%
“…Conjugate 2) can also enter target cells by receptor-mediated pinocytosis. This process involves the substrate binding to specific receptors on the plasma membrane and constitutes an efficient method of uptake at low substrate concentrations, although it typically shows receptor-saturation at high concentrations (Williams et al, 1975b).…”
Section: Assessment Of Release Of Liver Enzymesmentioning
confidence: 99%